Verbeniaside A, một sesquitecpen glycosit mới từ cây cỏ roi ngựa (Verbena officinalis L.) - Ngọc, Lành Thị; Hạnh, Trần Hồng; Minh, Châu Văn; Nam, Nguyễn Hoài; Hương, Hoàng Thanh; Cường, Nguyễn Xuân; Long, Phạm Quốc; Đạt, Nguyễn Tiến; Bản, Ninh Khắc; Giang, Vũ Hương; et al. (Vietnam Journal of Chemistry, 2012)
From the aerial parts of Verbena officinalis L. (Verbenaceae), a new sesquiterpene glycoside 12-hydroxynerolidol 12-O-[b-D-xylopyranosyl-(1®2)-b-D-glucopyranoside], named verbenaside A was isolated by various chromatography methods. Its chemical structure was elucidated by ESI-MS and 1D, 2D NMR experiments and by comparison of their NMR and ESI-MS data with previous reported data.